A comparative Study of Health Seeking Behaviour of Elderly in Rural and Urban Area of Prayagraj - Verma, Vandana; Prakash, Shiv; Parveen, Khurshid; Shaikh, Shama (National Journal of Community Medicine, 2021)
Background: Health of elderly is already a neglected area as general ageing comes with acceptance of diseases. The aim was to compare the health seeking behaviour of elderly in Prayagraj district in Uttar Pradesh. Methods: A cross sectional study was carried out on elderly aged 60 years and above; selected from urban and rural areas of Prayagraj district by multistage random sampling and were interviewed using pre tested schedule. Data analysis was done on SPSS 16 version. Results: A total of 400 elderly were surveyed, majority were lived in joint families (59%), illiterate (43.75%), and belonged to lower class (34.75%). More of urban elderly were seeking treatment (76%) than rural elderly (66%) whereas Allopathic therapy was preferred in both the group. In urban areas elderly prefer private facilities for the treatment (64.5%) whereas more of rural elderly preferred government health facilities (53%). The common cause of having no faith in government health services as stated by elderly in both rural (41.7%) and urban (29.3%) area was non availability of medicine. Conclusion: Over all the study showed that more of urban elderly seek treatment for their health problems as compared to rural elderly which could be attributed to inaccessibility to health care services.